ENVIRONMENTAL CONCEPT BASED PjBL (PROJECT BASED LEARNING) MODELS TO INCREASE THE OBSERVATION SKILLS OF VII GRADE STUDENTS AT SMPN 1 JENANGAN PONOROGO - Fauziah Hanin (Pendidikan IPA, FMIPA, UNP, 2020)
The purpose of this resreach is to determine the effect of environmental concept based PjBL (Project Based Learning) models to the observation skills of VII grade students at SMPN 1 Jenangan. This resreach was quantitative descriptive by Nonequivalent Control Group Design. The samples of this resreach were VII C (experimental) and VII D class (control) with a total 50 students. The instrument of this research was essay test. Essay test was applied before and after imlplementation of environmental concept based PjBL model. Data were analized by t-test using software minitab. The result showed that the P-value was 0,000; due to P-valu less than 0.05, so H0 was rejected. Its mean that, there was a significant differences between the student observations skills that use environmental concept based PjBL (Project Based Learning) models with the students observations skills that PBL (Problem Based Learning) model at SMPN 1 Jenangan.